Strategi Pengelolaan Agrowisata Pango-Pango Kabupaten Tana Toraja di Masa Pandemi Covid-19 - Mutmainnah Ali; Nasiah Badwi; Sukri Nyompa; Ramli Umar; Ichsan Invanni (UNIVERSITAS NEGERI MAKASSAR, 2022)
AbstractThe Covid-19 pandemic has an impact on all lines of people's lives, including the tourism sector, this makes tourism activities paralyzed and difficult to develop, one of which is affected is Pango-Pango agro-tourism in Tana Toraja Regency. This study aims to determine the Pango-Pango agro-tourism management strategy in Tana Toraja Regency during the Covid-19 pandemic. This type of research is descriptive qualitative research with sampling methods, namely purposive sampling and accidental sampling using descriptive statistical analysis and SWOT analysis. The results show that 1) the characteristics that exist in Pango-Pango agro-tourism can be presented in the form of attractiveness, accessibility and amenities, 2) the existing supporting factors are the strengths and opportunities, the inhibiting factors are the weaknesses and threats of Pango agro-tourism. -Pango, 3) Pango-Pango agro-tourism management strategy in Tana Toraja Regency during the Covid-19 pandemic based on a SWOT analysis using X (1.10) and Y (0.87) values located in quadrant I, namely the Rapid Growth Strategy. In order to deal with the Covid-19 pandemic, Pango-Pango agro-tourism pays attention to 3A, namely attractions, amenities and accessibility in order to attract tourists to the maximum. AbstrakPandemi Covid-19 berdampak pada semua lini kehidupan masyarakat, tidak terkecuali sektor pariwisata, hal ini membuat kegiatan pariwisata menjadi lumpuh dan sulit untuk dikembangkan, salah satu yang terkena dampaknya adalah agrowisata Pango-Pango di Kabupaten Tana Toraja. Penelitian ini bertujuan untuk mengetahui strategi pengelolaan agrowisata Pango-Pango Kabupaten Tana Toraja di masa pandemi Covid-19. Jenis penelitian ini adalah penelitian deskriptif kualitatif dengan metode pengambilan sampel yaitu purposive sampling dan accidental sampling menggunakan analisis statistik deskriptif dan analisis SWOT. Hasil penelitian menunjukkan bahwa 1) karakteristik yang ada di agrowisata Pango-Pango dapat di sajikan dalam bentuk daya tarik, aksesibilitas dan amenitas, 2) faktor pendukung yang ada yaitu yang menjadi kekuatan dan peluang, faktor penghambatnya yaitu yang menjadi kelemahan dan ancaman dari agrowisata Pango-Pango, 3) strategi pengelolaan agrowisata Pango-Pango Kabupaten Tana Toraja di masa pandemi Covid-19 berdasarkan analisis SWOT menggunakan nilai X (1,10) dan Y (0,87) terletak pada kuadran I yaitu Rapid Growth Strategy. Guna menghadapi pandemi Covid-19 agrowisata Pango-Pango memperhatikan 3A yaitu atraksi, amenitas dan aksesibilitas yang ada agar dapat menarik wisatawan secara maksimal.